Multistage separation processes - Khoury, Fouad M. (CRC Press, 2015)
The latest edition of a perennial bestseller, Multistage Separation Processes, Fourth Edition provides a clear and thorough presentation of the theoretical foundation, and understanding of the development, evaluation, design, and optimization steps of these processes, from both an academic and industrial perspective. The book's emphasis on starting with theoretical models and their role in computer simulation, followed by practical applications, sets it apart from other texts on this topic. The author also highlights the importance of relating fundamental concepts to intuitive understanding of the processes